STUDY ON QUALITY OF LIFE ASSESSMENT IN DIABETIC RETINOPATHY AMONG PATIENTS WITH TYPE 2 DIABETES - Vijayan, Meenu; Jose, Rose; Jose, Sruthy; Abraham, Suja; Joy, Jintu (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: The aim was to study the vision-related quality of life (QOL) for diabetic retinopathy (DR) among patients with Type 2 diabetes and to assess the direct medical cost of different treatment modalities. Methods: It was based on an individual-based analysis of QOL before and after the treatment for DR. The main objective of the study was to compare QOL between patients based on the different treatment modalities using vision function questionnaire (VFQ)-25, to evaluate the direct medical cost for DR patients undergoing different treatment modalities and to compare the cost and QOL of different treatment modalities in samples with non-proliferative DR (NPDR)/proliferative diabetic retinopathy (PDR) macular edema. The population included were patients with Type 2 diabetes with NPDR, with clinically significant macular edema and PDR, patients diagnosed to have diabetes above 5-year duration, adult patients, ocular pain those who are on regular follow-up and those who are willing to be a part of study. A total of 256 patients were selected out, of which 141 patients were satisfied the study criteria and participated in the study. Data relevant to the voice-related QOL study were obtained and recorded using VFQ-25 questionnaire. Other data relevant to the study were obtained and recorded in a semistructured data collection form by interviewing the patient or their caregivers and by direct examination of patient's medical record. Expenditure was calculated in Indian Rupees. Results: After comparing the baseline QOL with QOL after treatment, it was found that the overall QOL of the study samples in accordance with the treatment undergone was found to be improved. The overall QOL had improved after the treatment for all samples and major improvement was seen on dependency, social functioning (SF), and mental health (MH). Conclusion: The overall QOL had improved after the treatment for all samples and major improvement were seen on dependency, SF, and MH. In conclusion, the study analyzed that intravitreal bevacizumab therapy is the cheapest one and with the comparatively same clinical outcome when compared with intravitreal ranibizumab therapy for macular edema cases in patients with NPDR and PDR.